Strategi Promosi dan Peningkatan Omset Penjualan Pada Umkm Kain Tenun Khas Wabula Kabupaten Buton - Nining Asniar Ridzal; I Wayan Sujana; Ernawati Malik; Mudasir Ali Mahmud; Wa Ode Elfianti (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
Economic actors in Wabula Village, Buton Regency are actively developing the Wabula woven fabric business, but their activities are constrained by several things, namely related to advertising, production is still limited, conventional sales, no bookkeeping of businesses, lack of participation of the younger generation. These business actors lack the skills to promote their business which should be converted into sales. These problems became the basis for Community Service (PKM) activities. The method of implementing this activity is by analyzing the situation, coordinating, identifying the solution to partner problems, followed by seminars and training. So far, the promotion system carried out is still traditional promotion and seems passive, meaning that it waits for buyers to come. Awareness of using the internet for product promotion is still very low. This is because the craftsmen are parents who are technologically stuttering. For this reason, it is necessary to involve the younger generation who are technology literate. Until now, the focus of woven fabric craftsmen is still on the production and distribution process, so promotion is not a priority for business activities. As a result, the turnover obtained is not optimal. Regarding income, the craftsmen cannot mention because there is no detailed bookkeeping, nor is there a target. The lack of market share owned. This is due to the low promotion carried out and the marketing strategy is still conventional. For example, craftsmen only rely on production according to the number of orders, do not yet have ideas to add partners outside Wabula Village or use internet technology to sell.